THE INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON CONSUMER PURCHASING DECISIONS OF TOYOTA RUSH CARS IN MEDAN CITY CASE STUDY OF TOYOTA PERINTIS MEDAN CONSUMERS - Saragih, Andyka Rizky; Nasution, Satria Mirsya Affandy (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study was to determine the effect of product quality and brand image on the purchasing decisions of Toyota Rush Car customers in Medan City, either partially or simultaneously. This study uses a quantitative approach. The analysis technique used in this research is multiple linear analysis technique. The results of the study partially show that product quality has a significant effect on purchasing decisions of Toyota Rush Car customers in Medan City. Partially, brand image has a significant effect on purchasing decisions of Toyota Rush Car customers in Medan City. Simultaneously, product quality and brand image have a significant effect on purchasing decisions of Toyota Rush Car customers in Medan City. The R value is 0.882 or 88.2%, which means that the relationship between purchasing decisions and the independent variables, namely product quality and brand image, is close. The R-Square value in this research is 0.779, which means 77.9% of the variation in purchasing decisions is explained by the independent variables, namely product quality and brand image. While the remaining 22.1% is explained by other variables not examined in this study.